Social Media and Marketing Performance of Micro, Small And Medium Enterprises: The Moderating Role of Entrepreneurial Competencies - ANYADIGHIBE, JOSEPH AMAECHI; EFIONG, EME JOEL; KANKPANG, ALPHONSUS KECHI; INAH, EGU USANG; BESSONG, PETER KEKUNG; OGAR-ABANG, JOHN OYONG (Journal of Ecohumanism, 2024)
The study examined social media and marketing performance of micro, small and medium enterprises (MSMEs): The moderating role of entrepreneurial competencies. The study adopted cross-sectional survey research design. A structured questionnaire was used to obtain data from 327 operators of MSMEs. The hypotheses were tested using multiple linear regression and hierarchical regression. Findings from the study revealed that social network and media-sharing network had a significant positive effect on the marketing performance of MSMEs. It was also found that entrepreneurial competencies had a significant moderating effect on the relationship between social media and the marketing performance of MSMEs. The study recommends need for operators of MSMEs to intentionally acquire entrepreneurial competencies such as risk-taking, innovation, technical expertise and resilience through mentorship, personal development and sponsored skills acquisition programmes to enhance their marketing performance.